1999
DOI: 10.1046/j.1365-3083.1999.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐15 in Mycobacterial Infection of Antigen‐Presenting Cells

Abstract: Interleukin-15 (IL-15) shares many biological functions with IL-2 but also exhibits unique effects. Some of these represent the potent chemoattractant activity and expansion of distinct T-cell subsets, particularly memory T cells. IL-15 may therefore modulate the quality and quantity of cellular immune responses directed against intracellular pathogens. Immunohistochemical examination of skin lesions obtained from patients with the lepromatous or the tuberculoid form of Hansen's disease revealed intralesional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…The finding of increased IL-15 gene expression in the lungs of our patients with sarcoidosis is consistent with those of Muro and colleagues (26) and with experimental evidence linking IL-15 to macrophage-T-cell interactions in patients with active sarcoidosis (27). IL-15 expression in macrophages is regulated by IL-4 and GM-CSF, a mechanism favoring granuloma formation in the context of infections (28). IL-15 is highly expressed in alveolar macrophages derived from patients with sarcoidosis and is shown to induce the release of IFN-g from T cells (27).…”
Section: Discussionsupporting
confidence: 91%
“…The finding of increased IL-15 gene expression in the lungs of our patients with sarcoidosis is consistent with those of Muro and colleagues (26) and with experimental evidence linking IL-15 to macrophage-T-cell interactions in patients with active sarcoidosis (27). IL-15 expression in macrophages is regulated by IL-4 and GM-CSF, a mechanism favoring granuloma formation in the context of infections (28). IL-15 is highly expressed in alveolar macrophages derived from patients with sarcoidosis and is shown to induce the release of IFN-g from T cells (27).…”
Section: Discussionsupporting
confidence: 91%
“…IL-15 may represent a key cytokine involved in granuloma formation and may enhance cellular immune responses to mycobacterial antigens (15,50). Our data showed that macrophage differentiation in vitro with GM-CSF induced increased levels of IL-15, reinforcing our hypothesis that these cells exhibit the phenotype of macrophages found in paucibacillary patients.…”
Section: Discussionsupporting
confidence: 78%
“…Although IL-15 is constitutively expressed in cells of the monocyte/macrophage lineage, the expression of IL-15 mRNA has been shown to be up-regulated by LPS, poly I:C, as well as bacterial (12,81,82) and viral (83) infection. The present results show clearly that IFN-␥ is an important immune regulator of IL-15 in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The production of bioactive membrane bound or secreted IL-15 in mammals appears to be tightly controlled (81,84). Enhanced IL-15 protein production results from either increased transcription and/or stability of IL-15 mRNA, posttranslational modification, or altered cellular trafficking, and enhanced release of already preformed intracellular IL-15 protein.…”
Section: Discussionmentioning
confidence: 99%